Preferensi Koperasi Dalam Melakukan Konversi Menjadi Koperasi Syariah: Studi Kasus Pada Koperasi di Wilayah Bogor - Maya Apriyana; Sahlan Hasbi (Journal of Islamic Economics and Finance Studies, 2020)
This study aims to determine the most dominant factors affecting the cooperative preference in the conversion into a cooperative sharia. The research method using the quantitative approach to the technique of factor anaysis. The results indicate that regulatory support, promotion and profit sharing rate is the most dominant factor or a major factor for the preference of cooperative in the conversion into a cooperative sharia. Meanwhile religion, information, and image is a supporting factor for the preference of cooperatives in the conversion into a cooperative sharia.